Causal effects of psychostimulants on neural connectivity: a mechanistic, randomized clinical trial. (9th February 2022) - Wang, Yun; Kessel, Ellen; Lee, Seonjoo; Hong, Susie; Raffanello, Elizabeth; Hulvershorn, Leslie A.; Margolis, Amy; Peterson, Bradley S.; Posner, Jonathan
Abstract : Background: Psychostimulants are frequently used to treat attention‐deficit/hyperactivity disorder (ADHD), but side effects are common leading to many patients discontinuing treatment. Identifying neural mechanisms by which psychostimulants attenuate symptoms may guide the development of more refined and tolerable therapeutics. Methods: We conducted a 12‐week, randomized, placebo‐controlled trial (RCT) of a long‐acting amphetamine, lisdexamfetamine (LDEX), in patients with ADHD, ages 6–25 years old. Of the 58 participants who participated in the RCT, 49 completed pre‐ and post‐RCT magnetic resonance imaging scanning with adequate data quality. Healthy controls (HCs; n  = 46) were included for comparison. Treatment effects on striatal and thalamic functional connectivity (FC) were identified using static (time‐averaged) and dynamic (time‐varying) measures and then correlated with symptom improvement. Analyses were repeated in independent samples from the Adolescent Brain Cognitive Development study ( n  = 103) and the ADHD‐200 Consortium ( n  = 213). Results: In 49 participants (25 LDEX; 24 Placebo), LDEX increased static and decreased dynamic FC (DFC). However, only DFC was associated with the therapeutic effects of LDEX. Additionally, at baseline, DFC was elevated in unmedicated‐ADHD participants relative to HCs. Independent samples yielded similar findings – ADHD was associated with increased DFC, and psychostimulants with reduced DFC. Static FC findings were inconsistent across samples. Conclusions: Changes in dynamic, but not static, FC were associated with the therapeutic effects of psychostimulants. While prior research has focused on static FC, DFC may offer a more reliable target for new ADHD interventions aimed at stabilizing network dynamics, though this needs confirmation with subsequent investigations.